(3Pjd WHbGJ GdMfGHdIs - (3YHO GdQMef Hf CMeO Hf QLH GdMfHdj GdqSdGej GdHZOGOj Ke GdOeTbqj, CHh GdaQL, Rjf GdOjf,J (B795 (3g` s; (3eMeO Hf GdMSjf Hf eMeO Hf Nda GHf GdaQGA, CHh jYdj,J (B458 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf s
(3BNQgG (B:s
(3ced GdLRA GdKGfi hHg Je LejY GdcJGH s
(3LYd JQJjHg Ydi GdhajGJs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B99 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B254s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B138 s
Keywords: (3GdJGQjNs